2013
DOI: 10.1093/gerona/glt089
|View full text |Cite
|
Sign up to set email alerts
|

Aging, the Central Nervous System, and Mobility

Abstract: In addition to greater cross-disciplinary research, there is a need for new approaches to training clinicians and investigators, which integrate concepts and methodologies from individual disciplines, focus on emerging methodologies, and prepare investigators to assess complex, multisystem associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
197
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(212 citation statements)
references
References 54 publications
11
197
0
4
Order By: Relevance
“…It is reflected in the increase in reaction times [9] and movement times [10]. A recent research concluded that CNS may play a major role in mobility decline with aging [11]. Reduction in strength, endurance, flexibility and changes in strategies are motor problems leading to affection of postural response [12], [13].…”
Section: Literature Surveymentioning
confidence: 99%
“…It is reflected in the increase in reaction times [9] and movement times [10]. A recent research concluded that CNS may play a major role in mobility decline with aging [11]. Reduction in strength, endurance, flexibility and changes in strategies are motor problems leading to affection of postural response [12], [13].…”
Section: Literature Surveymentioning
confidence: 99%
“…4 The causes of mobility limitations are complex and multifactorial, involving many systems such as osteoarticular or cardiovascular systems, sensorial abilities, or the central nervous system. 5 A growing number of studies have focussed on the role of cardiovascular risk factors, by analogy with cognitive function. Dyslipidemia, diabetes mellitus, and hypertension have all been shown to be associated with poor physical performance.…”
Section: See Related Article Pp 340-346mentioning
confidence: 99%
“…Gait speed predicts the future onset of neurodegenerative diseases such as Alzheimer’s disease [6, 7]. Slow gait speed is related to a specific smaller volume of motor regions in the prefrontal cortex and basal ganglia [8, 9]. We hypothesized that the number of steps can predict an increase in the severity of PD.…”
Section: Introductionmentioning
confidence: 99%